A calibrated mechanics-based model for top-down cracking of asphalt pavements. (30th May 2019) - Ling, Meng; Luo, Xue; Chen, Yu; Hu, Sheng; Lytton, Robert L.
Highlights: Top-down cracking growth in asphalt pavements was characterized using fracture mechanics and Paris' law. Fracture and aging properties were recognized as two essential effects on top-down cracking propagation. Top-down cracking was identified as the precursor of fatigue cracking based on field performance. Transverse thermal stress was demonstrated to play a minor role in top-down cracking propagation. Abstract: A calibrated mechanistic-empirical model was developed to analyze top-down cracking (TDC) performance with actual traffic load and thermal stress. The traffic-induced and thermal-induced J-integral were employed in the Paris' law with fracture parameters A ′ and n ′ estimated using asphalt mixture properties. Number of days for initiated TDC to reach the medium severity level was then calculated mechanistically, which was related to field performance for calibration purposes. It was observed that when TDC reached a critical length, the TDC length diminished and area of fatigue cracking increased. An associated computer program was also developed, which normally completed a 30-year performance analysis within 1 min.